Physicochemical and Sensory Properties of Goat Meat Sausages Prepared With Different Levels of Goat Liver - Triyannanto, Endy; Rusman, Rusman; Cahyowati, Meireni; Kayihura, Joseph; Sitaresmi, Pradita Iustitia (Buletin Peternakan, 2024)
Anemia, a common issue among children and teenagers in Indonesia, is characterized by hemoglobin levels below normal. Iron is essential for producing hemoglobin in red blood cells, which helps prevent anemia. Innovation to provide a popular goat liver-based product that is convenient to consume and easily marketable underpins the development of this goat liver-enhanced sausage. The aim of this research was to determine the effect of partially substituting goat meat with different levels of goat liver on physicochemical and sensory properties of goat meat sausages. Sausages containing 100:0, 75:25, and 50:50 goat meat to goat liver ratios and goat meat (%, w/w) , and then added with other ingredients (tapioca flour, skim milk, garlic, pepper, coriander, salt, STPP, and ice water) were prepared and cooked for 30 minutes. The sausages were then analyzed for physical properties, including pH, texture and water holding capacity (WHC), iron content, and sensory quality. Data were analyzed using analysis of variance for a completely randomized design, and then if there were significant differences between means, they were tested using Duncan’s New Multiple Range Test. The results showed that substitution of goat liver significantly (p0.05). In conclusion, substituting up to 50% of goat meat with goat liver will improve the iron content of goat meat sausages with minimal impact on the sensory and proximate composition of the product.